VALIDITAS DAN KEPRAKTISAN E-MODUL BERBASIS STEM DENGAN MODEL PEMBELAJARAN LEARNING CYCLE 5E PADA SUBMATERI PENCEMARAN AIR UNTUK MELATIHKAN KETERAMPILAN BERPIKIR KREATIF - Sovie, Athalia; Anggorowati Rahayu, Dwi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Creative thinking skills were one of the essential 21st-century 4C competencies that needed to be developed. However, the results of the Programme for International Student Assessment (PISA) 2022 indicated that these skills remained a challenge in education, highlighting the need for instructional materials that could support their development. This study aimed to develop a valid and practical STEM-based e-module integrated with the Learning Cycle 5E instructional model on the water pollution subtopic to train students' creative thinking skills. This study employed a Research and Development (R&D) approach using the 4D model, which consisted of the define, design, develop, and disseminate stages. A limited trial was conducted on 24 students of class X at Wachid Hasyim 5 Senior High School Surabaya. The validity of the e-module was determined through expert validation, while its practicality was evaluated based on the implementation of learning activities and students' responses. Data collection techniques were carried out using validation methods, implementation observation, questionnaires and were analyzed descriptively using quantitative methods. The results showed that the e-module achieved a validity score of 96,16%, which was categorized as very valid. The practicality of the e-module was shown by the percentage of learning implementation of 94,12% and student responses of 98,33%, both of which were categorized as very practical. Based on these results, the STEM-based e-module integrated with the Learning Cycle 5E instructional model on the water pollution subtopic was considered valid and practical for training students' creative thinking skills.